Pakistan Development Update, April 2014 - World Bank (Washington, DC, 2014)
Pakistan's economy is weak but at a turning point. Growth recovery is underway, with the projected GDP growth approaching 3.6-4.0 percent, driven by dynamic manufacturing and service sectors, better energy availability, and early revival of investor confidence. Inflation is steady at 7.9 percent (y-o-y). The fiscal deficit is contained at around 6 percent of GDP due to improved tax collection and restricted current and development expenditure. The current account deficit remains modest, at around 1 percent of GDP, supported by strong remittances and export dynamism, and the external position is slowly improving since monetary and exchange rate policies switched gear toward rebuilding reserves last November. Performance under the IMF program remains satisfactory, with the 2nd Review concluded on March 24. Domestic and external risks, however, remain high, but are declining. Economic activity is gradually improving. Preliminary data for FY14 show growth picking up, driven mainly by services and manufacturing. A significant correction of a loose fiscal stance is taking place to ensure sustainability. Pakistan is on track to meet a fiscal deficit target of 5.8 percent of GDP in FY14. The external position is fragile but strengthening. The current account deficit was small, at around 1 percent of GDP by end-FY13 and remains so. In contrast, net official foreign exchange reserves declined to the equivalent of 1.3 months of imports at the end of June 2013 (bottoming down to 0.6 month of imports by the end of November 2013). Three sources of risk appear worrisome. Pakistan imports more than it exports, the latter being constrained by low productivity and competitiveness, limited access to reliable energy, and cumbersome business regulations.